Response to targeted cognitive training may be neuroprotective in patients with early schizophrenia. (30th June 2021) - Ramsay, Ian S.; Fryer, Susanna; Roach, Brian J.; Boos, Alison; Fisher, Melissa; Loewy, Rachel; Ford, Judith M.; Vinogradov, Sophia; Mathalon, Daniel H.
Highlights: Response to cognitive training coincided with changes in cortical thickness. Change in cortical thickness correlated across regions following training. Cortical thickness changes mediated thalamic volume and global cognition relationships. Abstract: Individuals with schizophrenia exhibit widespread cortical thinning associated with illness severity and deficits in cognition. However, intact cortical thickness (CTh) may serve as a protective factor. The current study sought to examine changes in CTh in response to auditory targeted cognitive training (TCT) in individuals with recent onset schizophrenia. Participants underwent MRI scanning and a cognitive assessment before and after being randomly assigned to 40 h of either TCT ( N = 21) or a computer games control condition (CG; N = 22) over 16 weeks. Groups did not differ at baseline on demographic variables or measures of CTh. At the level of group averages, neither group showed significant pre-post changes in CTh in any brain region. However, changes in CTh related to individual differences in treatment outcome, as improved global cognition in the TCT group corresponded to reduced cortical thinning in frontal, temporal, parietal, and occipital lobes. These relationships were not observed in the CG group. The current findings suggest that TCT may be neuroprotective in early schizophrenia, such that individuals who improved in response to training also showed a reduction in cortical thinning that may be otherwise hastened due to age and illness.